Significados e atribuições estabelecidos por licenciandos de Biologia sobre educação CTSA a partir de uma questão sociocientífica sobre déficit de polinização - Queiroz, Érica Lima Santos (2019)
In the context of teacher education, there are usually a number of challenges ahead of Science, Technology, Society and Environment (STSE) education. In this sense, education based on Socio-Scientific Issues (SSI) seeks to align with STSE education with a view to minimizing some of these difficulties, as well as minimizing transmissive teaching practices, which contribute little to the formation of critical and participatory citizens. With regard to education in science, we can organize in two major objectives of STSE education based on SSI, are: (i) training for the exercise of citizenship with the development of critical sense and (ii) socially responsible decision-making and socio-political actions aimed at greater social justice and environmental sustainability. However, we understand that, for this, it is essential to recognize relations between the STSE domains of SSI. The aim of the study was to "investigate the postures and knowledge mobilized by biology students in solving a SSI on pollination deficit, as well as the students' conceptions of STSE education and the use of SSI in science education." To achieve these purposes, we have developed a qualitative research in the case study approach. Data were collected through activities developed in groups with 18 students who collaborated with the research (one trio and three groups of 5 students) during an intervention in the subject of Supervised Internship in Science Teaching I. The data were collected through of documentary records of the activities developed, audio recordings of the discussions of these activities, and interview with a member of each group, which corresponds to 22% of the participants. Data analysis was carried out through adaptations of the Bardin content analysis and parameters proposed by Herreid for case construction. The results were discussed in the light of the theoretical references and they indicate the need to discuss more frequently the STSE relations in initial teacher training in order to favor future practices involving STSE education based on SSI in the school context, especially with regard to Case Study.